2022
DOI: 10.1039/d2nj02720h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of MoxFe1−xO nanocomposites for the ultra-fast degradation of methylene blue via a Fenton-like process: a green approach

Abstract: A detailed degradation study of methylene blue within 22 minutes by the green synthesis of MoxFe1−xO nanocomposites using Punica granatum peel extract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…X-ray diffraction (XRD) is a potent technique that is frequently employed and typically well known for qualitative and quantitative analyses of crystalline phases in materials; much more information can be obtained from a careful examination of the diffraction patterns such as the characterization of solid solutions, crystallite size and shape, crystal orientation, internal elastic strains/stresses at different levels. 72,73 Fig. 1 presents the XRD pattern of the synthesized nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray diffraction (XRD) is a potent technique that is frequently employed and typically well known for qualitative and quantitative analyses of crystalline phases in materials; much more information can be obtained from a careful examination of the diffraction patterns such as the characterization of solid solutions, crystallite size and shape, crystal orientation, internal elastic strains/stresses at different levels. 72,73 Fig. 1 presents the XRD pattern of the synthesized nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…5,6 Within this context of innovative green methodologies, plant-based synthesis of nanoparticles has enthused the researchers as they offer an environmentally benign pathway that can avoid the use of toxic additives, specically external reductants and capping agents as well as organic carcinogenic solvents. [7][8][9][10][11] The phytochemicals present in plants such as avones, terpenoids, ketones, aldehydes, amides, and carboxylic acids not only serve as excellent reductants but also as stabilising agents, imparting nanoparticles with considerable stability against agglomeration and oxidation. 12,13 Rao et al reported the synthesis of Fe°/Fe 3 O 4 nanoparticles using pomegranate (Punica granatum) leaf extract.…”
Section: Introductionmentioning
confidence: 99%